Measuring regional inequalities in Greek tourism development - Eleni Gaki; Stella Kostopoulou; Dimitris Lagos (European Regional Science Association (ERSA), 2013)
In recent times, the attention given to the importance of tourism as a particularly efficient way to promote regional development has significantly increased, owing to the capacity of tourism to create income and employment and to generate synergies within other economic sectors. Tourism is worldwide considered to have a key role in the economic development of regions, and therefore, is widely used to reduce regional disparities and to improve quality of life standards in local communities. Greece has a long tradition in tourism, mainly due to a gifted natural environment and rich cultural heritage. However, tourism development across regions is highly unbalanced. This is attributed particularly to the highly insular and mountainous geomorphology of the country, the uneven distribution of natural, socio-cultural and environmental resources, and the lack of appropriate regional and tourism development policies during the post war decades. The dominance of the mass tourism model adopted since the early seventies in the country and the extensive structural inefficiencies, are effectively hindering the existing potential for a balanced and viable tourism development. The main objective of this paper is to investigate tourism development disparities among Greek regions and to identify factors and occurring patterns that affect the tourism development of regions in order to formulate a strategy and policy framework for balanced regional tourism development. In the first section of this paper an overview of the theoretical approaches related to tourism and balanced regional development is provided. Next, the role of tourism in the Greek national economy and the country's position in the international tourism market are examined. Following an analysis of the evolution of regional tourism disparities in Greece during the last decades in the third section, quantitative techniques are used to assess intra- and cross-regional tourism inequalities in the fourth section. The results reveal the existence of strong regional disparities in tourism development among Greek regions, although the development pattern differs among different types of regions. Finally, in the last section some concluding remarks and policy recommendations are presented, leading to the identification of issues for further research.
Keywords: 330; Tourism development; regional inequalities; Greece